Strategi Pembelajaran Inkuiri dalam Meningkatkan Kemampuan Kerjasama dan Komunikasi dalam Pembelajaran PAI - Dwi Agus Prasetio; Abdul Khaliq Lubis; Gusmaneli Gusmaneli (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Inquiry learning strategies are the main focus in improving students’ collaboration and communication skills in Islamic Religious Education (PAI) learning. From the four studies mentioned, it is proven that the application of the inquiry model has succeeded in increasing students’ active learning, learning outcomes in the subject of moral aqidah, learning motivation, and students’ cognitive and psychomotor learning outcomes. The inquiry strategy not only increases students’ understanding of PAI material, but also encourages the development of collaboration and communication skills between students to achieve a better understanding. Thus, inquiry learning strategies are an effective choice for improving the quality of PAI learning by strengthening students’ social competence in the context of religious learning.